Kinetic and Surface Study of Single-Walled Aluminosilicate Nanotubes and Their Precursors - Mauricio Molina; María Teresa García-González; Mauricio Escudey; Nicolás Arancibia-Miranda (Nanomaterials, 2013)
The structural and surface changes undergone by the different precursors that are produced during the synthesis of imogolite are reported. The surface changes that occur during the synthesis of imogolite were determined by electrophoretic migration (EM) measurements, which enabled the identification of the time at which the critical precursor of the nanoparticles was generated. A critical parameter for understanding the evolution of these precursors is the isoelectric point (IEP), of which variation revealed that the precursors modify the number of active ≡Al-OH and ≡Si-OH sites during the formation of imogolite. We also found that the IEP is displaced to a higher pH level as a consequence of the surface differentiation that occurs during the synthesis. At the same time, we established that the pH of the reaction (pHrx) decreases with the evolution and condensation of the precursors during aging. Integration of all of the obtained results related to the structural and surface properties allows an overall understanding of the different processes that occur and the products that are formed during the synthesis of imogolite.